2010
DOI: 10.1101/cshperspect.a000364
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Function of Bacterial Actin Homologs

Abstract: During the past decade, the appreciation and understanding of how bacterial cells can be organized in both space and time have been revolutionized by the identification and characterization of multiple bacterial homologs of the eukaryotic actin cytoskeleton. Some of these bacterial actins, such as the plasmid-borne ParM protein, have highly specialized functions, whereas other bacterial actins, such as the chromosomally encoded MreB protein, have been implicated in a wide array of cellular activities. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
70
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 94 publications
(143 reference statements)
0
70
1
1
Order By: Relevance
“…The deletion of MreB, or the inhibition of MreB polymerization using the drug A22, leads to spherical cells that are prone to lysis and have an altered cell wall structure (5,8,9). During elongation, we observed that MreB has a preference to localize to regions of small or even negative local Gaussian curvature.…”
Section: Introductionmentioning
confidence: 87%
“…The deletion of MreB, or the inhibition of MreB polymerization using the drug A22, leads to spherical cells that are prone to lysis and have an altered cell wall structure (5,8,9). During elongation, we observed that MreB has a preference to localize to regions of small or even negative local Gaussian curvature.…”
Section: Introductionmentioning
confidence: 87%
“…Of the bacterial cytoskeletal proteins, the widely conserved actin homolog MreB is particularly important for bacterial cells to elongate and maintain a rod-like shape. MreB forms polymers that are associated with the cell membrane and distributed along the length of the cell in many rod-shaped bacteria (2). These polymeric MreB structures are essential for the maintenance of rod-like cell shape, as their disruption leads to cell rounding.…”
mentioning
confidence: 99%
“…There are, in contrast, at least 30 distinct families of Alps that are encoded on a variety of mobile genetic elements, and many of these Alps perform the same function. For example, Alp7A, AlfA, and ParM represent three distantly related families of Alps; they are encoded on three different plasmids, yet they all segregate plasmids (1,4,27,32,47). Their identical function notwithstanding, these Alps have been shown to differ in their cell biological and in their biophysical properties (1,4,10,11,26,32).…”
mentioning
confidence: 99%
“…There is regulation of actin function and activity in other actin-based plasmid segregation systems, but it can be of a very different sort. In the parMR operon of the Escherichia coli plasmid R1, for example, the parM gene codes for another bacterial actin that is distantly related to eukaryotic actin, to the alp7 family, and to the other bacterial actin families (4,12,13,45,47). ParM, like Alp7A, is a plasmid segregation determinant, and filaments of both this prototypical ParM and the ParM of plasmid pB171 exhibit dynamic instability (10,11,34,37,41).…”
mentioning
confidence: 99%
See 1 more Smart Citation